ANALISIS PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL MENENGAH DALAM LAPORAN KEUANGAN USAHA MIKRO KECIL MENENGAH - Santi, Julia; Efriyenti, Dian (SCIENTIA JOURNAL, 2020)
In the current economic development, micro, small and medium enterprises are making rapid progress. This requires business actors to be able to make financial reports based on SAK EMKM. The purpose of this study is to determine the accounting recording process for MSME entrepreneurs, then find out the accounting records for MSMEs in Sekupang sub-district have implemented SAK EMKM and what obstacles are faced by MSMEs actors in implementing SAK EMKM. The method in this research is descriptive qualitative by collecting data observatively, interviews with research related parties. By using Purposive sampling from 312 populations 3 MSMEs were taken as samples. The results of this study are the SMEs in Batam have implemented a good and complete accounting record, MSMEs in Sekupang sub-district have applied SAK-EMKM-based financial reports in the financial statements of MSME actors. Lack of socialization by the Cooperative Office regarding reporting standards for MSMEs in Batam city and the limited number of human resources to assist in arranging MSMEs financial reports.